The enantioselective toxicity and oxidative stress of beta-cypermethrin on zebrafish. (October 2017) - Mu, Xiyan; Shen, Gongming; Huang, Ying; Luo, Jianbo; Zhu, Lizhen; Qi, Suzhen; Li, Yingren; Wang, Chengju; Li, Xuefeng
Abstract: Although the toxicity of beta-cypermethrin (beta-CYP) to aquatic organisms has become a significant concern in recent years, its enantioselective effects on non-target organisms is poorly understood. To investigate the enantioselective toxicity of beta-CYP on zebrafish, adult zebrafish were exposed to a series of isometric concentrations of four beta-CYP enantiomers and the beta-CYP racemate for 96 h. In addition, the activities of four antioxidant enzymes and the malondialdehyde (MDA) content in zebrafish liver and brain were tested after 15 and 30 days beta-CYP enantiomers and racemate exposure under environmentally relevant dosages (0.01 and 0.1 μg / L). According to the acute toxicity results, the 1 R - cis -α S and 1 R - trans -α S enantiomers were more lethal than 1 S - cis -α R and 1 S - trans -α R . At 0.1 μg / L, the 1 R - cis -α S and 1 R - trans -α S enantiomers, and the beta-CYP racemate could significantly induce a hepatic MDA content at 30 days post exposure (dpe), while only 1 R - cis -α S caused brain lipid peroxidation. An apparent regulation of antioxidase levels was observed in zebrafish liver and brain after exposure to the 1 R - cis -α S and 1 R - trans -α S enantiomers, and the beta-CYP racemate. In contrast, no significant oxidative stress was observed in zebrafish exposed to 1 S - cis -α R and 1 S - trans -α R enantiomers under the test concentrations. This work demonstrated the occurrence of enantioselectivity in toxicity and oxidative stress of beta-CYP to adult zebrafish, which should be considered in environmental risk assessments. Graphical abstract: Highlights: The toxicity of 1 R - cis -α S and 1 R - trans -α S enantiomers are much higher than 1S-cis-αR and 1S-trans-αR. 1 R-cis-αS, 1 R-trans-αS enantiomers and racemate could induce significant oxidative stress in zebrafish liver and brain. The effective dosage of 1 R - cis -α S enantiomer is lower than detected cypermethrin concentration. Abstract : There is a sharp discrepancy of lethality and oxidative stress among the four enantiomers of beta-cypermethrin.